Social media as a promotional tool towards SME's development evidence from the financial industry in a developing economy - John Amoah; Abdul Bashiru Jibril (Cogent Business & Management, 2021)
The notable contribution of small and medium enterprises (SMEs) in the development of socio-economics has been very encouraging in terms of its GDP contribution and employment creation. Both developed and developing countries are living testimonies of the contributions by SMEs. The primary aim of this paper is to assess the use of social media as a promotional tool for SME development. To achieve this objective, a total of 800 structured questionnaires were developed through an intercept and online survey to obtain data for the exercise. A non-probability sampling technique was employed for the collection of the data of which 648 respondents were dully accurate for the data processing/analysis. Using PLS-SEM with the help of ADANCO software v 2.2.1, findings revealed that the use of social media as an advertising tool has a significant effect on a firm's financial performance, business motivation, customers' perspective/attraction, and an increase in market share, thus, a key in reflecting a positive change in their marketing and promotional activities in the consumer market. The findings of the study are both beneficial to practitioners/owners of SMEs and the social media marketing literature in general. This study further strengthens the need for businesses to invest in digital marketing tools and employ them effectively to stay competitive in the long term for the firm's growth and survival.
Keywords: 650; Social media; advertising; promotion tool; SME's; financial industry; ghana